Measuring and explaining health and health care inequalities in Jamaica, 2004 and 2007 Medición e interpretación de las desigualdades en la salud y la atención sanitaria en Jamaica, 2004 y 2007 - Ewan Scott; Karl Theodore (Pan American Health Organization, 2013)
OBJECTIVE: This study addresses the need to measure and explain the inequalities and inequities of Jamaica's health system to generate evidence to support policy development, monitoring, and evaluation. METHODS: The nationally representative Jamaica Survey of Living Conditions data sets for 2004 and 2007 were used to produce concentration curves and concentration indices for three health outcome variables (probability of any illness or injury, duration of latest episode of -illness, and self-assessed health status) and two health care utilization variables (probability of a curative visit to a health practitioner and number of curative visits) to measure income-related inequalities. Their standardized counterparts were used to measure inequities. Decomposition of the concentration index provides a basis for explaining the contributions of socioeconomic and demographic factors to overall inequalities. RESULTS: Probability of illness and duration of illness were concentrated among the poor, while there was a distinct pro-rich inequality with respect to utilization of heath care services. These inequalities and inequities became more pronounced over the period 2004 - 2007. The level of household welfare was found to be the single most significant factor contributing to these inequalities. Other significant contributing factors were unemployment and rural location for health outcomes and insurance coverage for utilization of services. CONCLUSIONS: In spite of measures taken ostensibly to address health equity in Jamaica, income-related inequalities in health outcomes and health care have increased and the population group that needs health services most is using them least. These findings suggest a need for more innovative programs geared toward improving equity in health in Jamaica. OBJETIVO. Medir y explicar las desigualdades y las inequidades del sistema de -salud de Jamaica a fin de obtener evidencia que apoye el desarrollo, el seguimiento y la evaluación de las políticas de salud. MÉTODOS. Se usaron los datos ...